Antibiotic resistance and pathogenicity assessment of various Gardnerella sp. strains in local China - Zhang, Kundi; Lu, Mengyao; Zhu, Xiaoxuan; Wang, Kun; Jie, Xuemei; Li, Tan; Dong, Hongjie; Li, Rongguo; Zhang, Fengyu; Gu, Lichuan (Frontiers in Microbiology, 2022)
Gardnerella overgrowth is the primary cause of bacterial vaginosis (BV), a common vaginal infection with incidences as high as 23–29% worldwide. Here, we studied the pathogenicity, drug resistance, and prevalence of varying Gardnerella spp. We isolated 20 Gardnerella strains from vaginal samples of 31 women in local China. Ten strains were then selected via phylogenetic analysis of cpn60 and vly gene sequences to carry out genome sequencing and comparative genomic analysis. Biofilm-formation, sialidase, and antibiotic resistance activities of the strains were characterized. All strains showed striking heterogeneity in genomic structure, biofilm formation and drug resistance. Two of the ten strains, JNFY3 and JNFY15, were classified as Gardnerella swidsinskii and Gardnerella piotii, respectively, according to their phenotypic characteristics and genome sequences. In particular, seven out of the ten strains exhibited super resistance (≥ 128 μg/mL) to metronidazole, which is the first line of treatment for BV in China. Based on the biochemical and genomic results of the strains, we proposed a treatment protocol of prevalent Gardnerella strains in local China, which provides the basis for accurate diagnosis and therapy.